Validating the GTP-cyclohydrolase 1-feedback regulatory complex as a therapeutic target using biophysical and in vivo approaches. - Hussein, D; Starr, A; Heikal, L; McNeill, E; Channon, K; Brown, P; Sutton, B; McDonnell, J; Nandi, M (Wiley, 2015)
BACKGROUND AND PURPOSE: 6R-L-erythro-5,6,7,8-tetrahydrobiopterin (BH4 ) is an essential cofactor for nitric oxide biosynthesis. Substantial clinical evidence indicates that intravenous BH4 restores vascular function in patients. Unfortunately, oral BH4 has limited efficacy. Therefore, orally bioavailable pharmacological activators of endogenous BH4 biosynthesis hold significant therapeutic potential. GTP-cyclohydrolase 1 (GCH1), the rate limiting enzyme in BH4 synthesis, forms a protein complex with GCH1 feedback regulatory protein (GFRP). This complex is subject to allosteric feed-forward activation by L-phenylalanine (L-phe). We investigated the effects of L-phe on the biophysical interactions of GCH1 and GFRP and its potential to alter BH4 levels in vivo. EXPERIMENTAL APPROACH: Detailed characterization of GCH1-GFRP protein-protein interactions were performed using surface plasmon resonance (SPR) with or without L-phe. Effects on systemic and vascular BH4 biosynthesis in vivo were investigated following L-phe treatment (100 mg·kg(-1) , p.o.). KEY RESULTS: GCH1 and GFRP proteins interacted in the absence of known ligands or substrate but the presence of L-phe doubled maximal binding and enhanced binding affinity eightfold. Furthermore, the complex displayed very slow association and dissociation rates. In vivo, L-phe challenge induced a sustained elevation of aortic BH4 , an effect absent in GCH1(fl/fl)-Tie2Cre mice. CONCLUSIONS AND IMPLICATIONS: Biophysical data indicate that GCH1 and GFRP are constitutively bound. In vivo, data demonstrated that L-phe elevated vascular BH4 in an endothelial GCH1 dependent manner. Pharmacological agents which mimic the allosteric effects of L-phe on the GCH1-GFRP complex have the potential to elevate endothelial BH4 biosynthesis for numerous cardiovascular disorders.